2019
DOI: 10.1051/0004-6361/201834987
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of two spectral breaks in the prompt emission of gamma-ray bursts

Abstract: The long-lasting tension between the observed spectra of gamma-ray bursts (GRBs) and the predicted synchrotron emission spectrum might be solved if electrons do not completely cool. Evidence of incomplete cooling was recently found in Swift GRBs with prompt observations down to 0.1 keV, and in one bright Fermi burst, GRB 160625B. Here we systematically search for evidence of incomplete cooling in the spectra of the ten brightest short and long GRBs observed by Fermi. We find that in eight out of ten long GRBs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 41 publications
9
75
0
Order By: Relevance
“…The fact that the majority of the spectra of bright long GRBs can be fitted with the above mentioned three-power law model (Oganesyan et al 2017;Ravasio et al 2018Ravasio et al , 2019 indeed suggests that the synchrotron process is the radiative mechanism originating the prompt emission. This implies that the emitting particles do not cool completely (Daigne, Bosnjak & Dubus 2011), but "remain" at the energy γ cool for a timescale comparable to the typical time bin of the time resolved spectral analysis (∼ 1 s).…”
Section: Introductionmentioning
confidence: 95%
“…The fact that the majority of the spectra of bright long GRBs can be fitted with the above mentioned three-power law model (Oganesyan et al 2017;Ravasio et al 2018Ravasio et al , 2019 indeed suggests that the synchrotron process is the radiative mechanism originating the prompt emission. This implies that the emitting particles do not cool completely (Daigne, Bosnjak & Dubus 2011), but "remain" at the energy γ cool for a timescale comparable to the typical time bin of the time resolved spectral analysis (∼ 1 s).…”
Section: Introductionmentioning
confidence: 95%
“…So, after a decade from 2009, the main component that shapes the GRB prompt emission spectra is identified 23,25,27,28,30 . With detailed observations and data analyses of the broad-band prompt emission data (γ-rays, X-rays and optical) of many GRBs using the current and future GRB observatories, it would be possible to quantify the distribution of the GRB jet composition in the future.…”
mentioning
confidence: 99%
“…Direct fits of the synchrotron emission model to GRB prompt spectra have been performed by Zhang et al (2016) and Burgess (2019), who showed that the line-of-death and spectralsharpness issues are likely artefacts due to the use of the Band function (see also Ronchi et al 2020). Fitting the spectra with simpler versions of the synchrotron emission model or with empirical functions featuring a low-energy spectral break, especially on a broad energy range extending down to the X-ray and/or optical domain, appears able to reconcile the observations with the synchrotron theory as well, showing the expected transition from fast to slow cooling (Oganesyan et al 2017(Oganesyan et al , 2018(Oganesyan et al , 2019Ravasio et al 2018Ravasio et al , 2019.…”
Section: Introductionmentioning
confidence: 91%